Legal Arrangements Regarding Dispute Resolution Through Mediation In Civil Cases - Sri Anggraini Kusuma Dewi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
Settlement of land disputes can be done through mediation or a peace process, meaning that the parties to the dispute submit the resolution to a mediator to achieve a fair final result, without wasting huge costs. The requirement to carry out mediation applies to court case processes, both in general and religious courts. One of the provisions of article 2 of the Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court is that the provisions that must not be ignored are that the decision is null and void if the mediation procedure is not carried out based on the Republic of Indonesia Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. Article 3 (2) of the Republic of Indonesia Supreme Court Regulations states that the Case Examining Judge in considering the decision must state that efforts have been made to reconcile the case through mediation by naming the mediator. This article will review mediation in civil cases. The implementation of the Republic of Indonesia Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court, which can be the main option in resolving civil cases so as to reduce the buildup of the number of civil cases in court and be more profitable.